Ethnographies of law and social control - Burns, Stacy Lee (Sociology of crime, law, and deviance, 2005)
Bringing together scholars and experts in ethnography, law, and social control, this collection presents an overview of the everyday work and activities of legal and social control professionals, functionaries, and participants. It emphasizes the need to consider the organizationally and institutionally specific features and competencies.